Measure of Machine Strength by Erlang Distribution - Gokdere, Gokhan; Gurcan, Mehmet (Amer Inst Physics, 2016)
In this study, possible states for the components are considered under stress-strength model which makes the components multi-state. The probabilities of components are studied when strengths of the components are Erlang random variables and the stresses are independent exponential random variables. The probabilities of components are considered when the stresses are dependent exponential random variables.
International Conference on Numerical Analysis and Applied Mathematics (ICNAAM) -- SEP 23-29, 2015 -- Rhodes, GREECE
Keywords: Reliability Evaluation